Youth physical activity is all about the "F-words" - Faigenbaum, A. D.; Rebullido, T. R.; Chulvi-Medrano, I. (Strength and Conditioning Journal, 2020)
The "F-words" of youth physical activity (family, facilitators, facilities, force, fitness, function, fun, feeling, and future) illustrate the complex web of factors that influence participation in active play, exercise, and sport activities in children and adolescents. The "F-words" can be used to expand our conceptual thinking about youth physical activity and inform research and practice in the field of pediatric exercise science.